Modelling the spatial and genetic response of the endemic sparid: Polysteganus praeorbitalis (Pisces: Sparidae) to climate change in the Agulhas Current system - Isemonger, Devin Neil (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2014)
The Scotsman Seabream, Polysteganus praeorbitalis, is one of several large, slow-growing members of the Sparidae family of fishes endemic to the Agulhas Current system in the Western Indian Ocean (WIO). Relatively little research has been conducted on this species despite its importance to both recreational and commercial line fisheries in South Africa and the drastic decline in catch per unit effort (CPUE) that has been recorded since the 1940s. Changing sea temperatures as a result of global climate change are further expected to affect the distribution and abundance of many fish species based on their thermal tolerances, life histories and population structures. The ability of these species to shift their distribution and adapt to new environments and thermal conditions will depend to some degree on the levels of genetic variation and gene flow, within and between populations. A combined approach using species distribution modelling and genetic analyses may prove to be a useful tool in investigating the potential effects of climate change on the distribution and genetic diversity of species. An ensemble species distribution model (SDM) based on 205 occurrence records and 30 years of Reynolds Optimum Interpolated (OI) sea surface temperature data was constructed to predict the distributional response of P. praeorbitalis to climate change in the Agulhas Current system. The ensemble SDM displayed a true skill statistic (TSS) of 0.975 and an area under the receiver operating curve (ROC) of 0.999, indicating good model fit. Autumn and winter minimum temperatures, as well as bathymetry, were the most important predictor variables in the majority of models, indicating that these variables may directly constrain the distribution of P. praeorbitalis. In particular, the southern range edge of this species appeared to be constrained by autumn and winter minima, with high model agreement on this range edge. Conversely, the northern range limit showed poor model agreement leading to a gradual reduction in occurrence. This indicates that this range edge may be constrained by other factors not included in the models such as species interactions. The ensemble SDM projected the current range of P. praeorbitalis to be 1500 kmÂ², smaller than the published range for this species. The model underestimated the northern range edge of this species by approximately 5Â° latitude when binary transformed. This is probably due to the rarity of this species in the landings of the Mozambican linefishery, which was assumed to be an indication of low abundance of P. praeorbitalis in these waters. The absence of a specimen to verify the published northern range edge of this species indicates that the northern range edge produced by this model is likely to be closer to the actual range limit of the species. A range contraction of 30% occurring at both the northern and southern edge of P. praeorbitalis' range and range fragmentation occurring, towards its northern range edge by 2030, was predicted. These changes are modelled to be the results of cooling related to the intensification of the Port Alfred upwelling cell and of warming predicted north of the Natal Bight and in southern Mozambique. Genetic analyses of the nuclear DNA (nDNA) S7 intron 1 and mitochondrial DNA (mtDNA) control region genes were carried out using 118 tissue samples of P. praeorbitalis collected at four main localities: the Eastern Cape, Transkei, southern KwaZulu-Natal and northern KwaZulu-Natal. Analyses of genetic diversity levels revealed relatively low diversity in the mtDNA dataset (Hd = 0.488; Ï€ = 0.004) and moderate levels of diversity in the nDNA dataset (Ad = 0.922; Ï€ = 0.005). The low levels of diversity observed in the mtDNA dataset might be explained by a number of factors, including high variation in spawning success, the negative effects of over-harvesting, or a recent population bottleneck. The last explanation is supported by characteristic star-shaped haplotype networks and unimodal mismatch distributions displayed by both datasets. These results, in conjunction with a significant (p = 0.005) negative Tajimas D value (-2.029) in the mtDNA dataset and significant (p = 0.0005) negative Fu's F statistic in both the nDNA (F = -26.5) and mtDNA (F = -11.9) datasets, provide strong evidence for a recent population expansion after a bottleneck event in this species. Spatially, mtDNA diversity was highest in the Eastern Cape and lowest in the middle localities, while nDNA diversity showed the opposite pattern. These results may be indicative of differences in the sex ratio between localities, possibly as a result of the protogynous hermaphroditism that has been postulated for this species. Although pairwise comparisons and exact tests of population differentiation revealed no significant geneticdifferentiation between populations in the mtDNA dataset, there was some evidence of low levels of differentiation in the nDNA dataset. This occurred for comparisons between the Eastern Cape and Transkei (Fst = 0.039; p <0.05), and the northern KwaZulu-Natal (Fst = 0.045; p < 0.05).. This might be the result of one or a combination of factors including the effects of the Port Alfred upwelling cell on dispersal and gene flow, or the possibility of more than one spawning ground for this species promoting sub-structuring. A SAMOVA analyses run on the nDNA dataset maximised variance by grouping the Eastern Cape and southern KwaZulu-Natal together and Transkei and northern KwaZulu-Natal together in two groups. This revealed no evidence of spatial structure (p = 0.36), with only 3.30% of variation explained by this grouping. The removal of individuals below the estimated length at 50% maturity in the nDNA dataset, in order to test for temporal structure, resulted in stronger evidence of differentiation between the Eastern Cape and all other localities: Transkei (Fst = 0.081; p< 0.05), southern KwaZulu-Natal (Fst = 0.031; p<0.05), and northern KwaZulu-Natal (Fst = 0.078; p< 0.05). This indicates that some temporal genetic structure may exist between age classes within this species. The differentiation observed between the Eastern Cape and other localities, coupled with the high percentage of private haplotypes in the mtDNA dataset in this locality, indicates that this area is where P. praeorbitalis is most vulnerable to the potential negative effects of climate change on its genetic diversity. However, the vast majority of this species genetic diversity appears to reside towards the centre of its range where it is most abundant and the lack of strong genetic structure indicates high levels of gene flow. In conclusion, while P. praeorbitalis is vulnerable to range loss as a result of climate change, its genetic diversity is unlikely to be greatly affected.
Keywords: Uncatalogued